1983
DOI: 10.1099/00221287-129-4-1121
|View full text |Cite
|
Sign up to set email alerts
|

The Endoparasitic Nematophagous Fungus Meria coniospora Infects Nematodes Specifically at the Chemosensory Organs

Abstract: Conidia of the endoparasitic fungus Meria coniospora infected the bacterial-feeding nematode Panagreflus rediviuus at specific sites, namely the mouth region and in male nematodes also in the tail. Plant-parasitic nematodes were also infected in other parts of the body. The specific infection sites in P. redivivus were the sensory organs, which are the sites of chemoreception.Blocking of chemoreceptors by adhered conidia of M . coniospora caused a complete loss of the ability of nematodes to be attracted to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Previous studies with Acrobeloides spp. showed that adhesion, if observed, almost invariably occurred in the mouth region, but seldom in other parts of the nematode [1]. In our study adhesion to the nematode body also occurred, although less abundantly than to the mouth region.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Previous studies with Acrobeloides spp. showed that adhesion, if observed, almost invariably occurred in the mouth region, but seldom in other parts of the nematode [1]. In our study adhesion to the nematode body also occurred, although less abundantly than to the mouth region.…”
Section: Discussionsupporting
confidence: 59%
“…With P. redivivus, germination of conidia of D. coniospora and penetration of the cuticle occurs within 1 h after adhesion [3]. A delay in penetration following adhesion has been observed after treatment of different species of mainly plant and animal parasitic nematodes with conidia of D. coniospora [1,5,6]. This indicates that adhesion itself is not sufficient to facilitate infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duveau, 2012). It can infect a broad range of nematode species (Jansson and Nordbring-Hertz, 1983), suggesting that it likely infects C. elegans naturally. Jansson et al (1985), Jansson (1994), F elix and Duveau 2012Bacteria Leucobacter musarum japonicus a…”
Section: Parasite Adaptation and Virulencementioning
confidence: 99%
“…coniospora spores can adhere to the head of a nematode, then extend hyphae into the body, via the open ends of sensory neurons [13,14]. For the first day or two, the worms appear healthy, but then die and rapidly become engulfed by the hyphae that sprout from the inside (Fig.…”
Section: Elegans As a Hostmentioning
confidence: 99%